Complexities of Spiritual Care in Plural Societies Education, Praxis and Concepts - Hege Grung, Anne (Studies in Spiritual Care, 2022)
This volume contributes to an emerging field that could be referred to as "plural spiritual care and chaplaincy". It's innovative approach brings together contributions from a broad range of contexts and religious traditions and includes empirical work and conceptual explorations. It helps to fill the gap between practices and developments related to plural spiritual care and chaplaincy in the scholarly discourse.